-21.2=p-12.7

Simple and best practice solution for -21.2=p-12.7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -21.2=p-12.7 equation:


Simplifying
-21.2 = p + -12.7

Reorder the terms:
-21.2 = -12.7 + p

Solving
-21.2 = -12.7 + p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1p' to each side of the equation.
-21.2 + -1p = -12.7 + p + -1p

Combine like terms: p + -1p = 0
-21.2 + -1p = -12.7 + 0
-21.2 + -1p = -12.7

Add '21.2' to each side of the equation.
-21.2 + 21.2 + -1p = -12.7 + 21.2

Combine like terms: -21.2 + 21.2 = 0.0
0.0 + -1p = -12.7 + 21.2
-1p = -12.7 + 21.2

Combine like terms: -12.7 + 21.2 = 8.5
-1p = 8.5

Divide each side by '-1'.
p = -8.5

Simplifying
p = -8.5

See similar equations:

| .333h-4(.666h-3)=.666h-6 | | 8-5n=-7 | | 18a^6-25a^5+8a^4=0 | | 4n+12=2 | | 4x-2/3=x+2 | | 4s-1=8-2a | | -(3x-5)=2 | | 35y^4-205y^3+150y^2=0 | | y-7=-4x-4 | | (9y^2)-12y+1=0 | | 2x^4-24x^3+54x^2=0 | | 6m=8-9-6m | | 5t-3=8t-12 | | 2r+8-1=-3 | | 6h+4g=77 | | -x-2x=-8 | | (4y^2)+7=12y | | 15x^3-102x^2-144x=0 | | .5+5x=7x-18 | | V=Len | | -6(v+4)+4v+7=8v+7 | | 2-5(x+5)=(x+2)-1 | | 3-7d+2d=-2-2(1-d) | | 5(m+3)+7m=3(m-10) | | 14x^3+39x^2+10x=0 | | 4g+6h=77 | | 6m-14=-8 | | -8m+73-6(m-3)=9m-(2m-6)-5m+5 | | 6w+5-5w=8-2 | | 2(3x-8)+10=-30 | | 5k+2=17 | | -2(-5v-6)-(1+10V)= |

Equations solver categories